1990
DOI: 10.1093/nar/18.3.577
|View full text |Cite
|
Sign up to set email alerts
|

B to Z transitions of the short DNA hairpins formed from the oligomer sequences: d[(CG)3×4(CG)3] (X = A, T, G, C)

Abstract: Circular Dichroism (CD) spectra were collected as a function of sodium perchlorate concentration [NaClO4] for the set of DNA hairpins formed from the oligomer sequences d[(CG)3X4(CG)3] where X = A, T, G or C. Over the range in salt concentration from 0 to 4.0 M NaClO4, the CD spectra invert in a manner characteristic of the B to Z transition. A factor analysis routine is described and employed to determine the least number of basis spectra required to fit the measured spectra of each hairpin over the entire sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Additionally it was found that homomismatches of C-C pairing are energetically more favourable than other hetero mismatches explaining this unusual stability [33]. The observed CD spectrum can be brought into accordance with a hairpin B-DNA structure [32] and it can be also assumed that the T-A pairing, which has been validated by the results of Fig. 2 and Fig.…”
Section: Resultssupporting
confidence: 70%
“…Additionally it was found that homomismatches of C-C pairing are energetically more favourable than other hetero mismatches explaining this unusual stability [33]. The observed CD spectrum can be brought into accordance with a hairpin B-DNA structure [32] and it can be also assumed that the T-A pairing, which has been validated by the results of Fig. 2 and Fig.…”
Section: Resultssupporting
confidence: 70%
“…This interpretation is further supported by the CD of short oligonucleotides in the presence of ZR. Unmodified hairpins with a stem built by merely three d(CG) dinucleotide steps can be completely flipped from B to Z at room temperature in 4 M NaClO 4 (46). In contrast, the ZR peptide used in these studies shows a less pronounced effect.…”
Section: Discussionmentioning
confidence: 90%
“…53 Factor analysis treats the CD spectra as a set of vectors and then, without imposing external constraints, solves for an orthogonal set of subspectra or basis vectors that can be linearly combined to construct the original set of spectra. For each molecule, the input data were the D" values measured every 0.2 nm from 205.2 to 320 nm comprising the CD spectrum.…”
Section: Analysis Of CD Spectramentioning
confidence: 99%